Hetero-bonding strength investigation into opto-mechanical interface - Hu, Haifei; Zhou, Di; Zhao, Chenchen; Qi, Erhui; Luo, Xiao (Frontiers in Astronomy and Space Sciences, 2024)
Glass-metal hetero-bonding through optical epoxy adhesive is frequently used in opto-mechanics and requires high stability. However, the bonding stability is difficult to achieve and predict in massive use cases, where dozens to thousands of metal pads are bonded to mount large optics. Here a universal adhesive bonding technology was proposed and evaluated through reliability analyses based on a limited number of sample tests. Specimens were prepared and tested via standard procedures and equipment; afterward, the lower strength limits were calculated with high reliability. Nominal tensile (6.7 MPa) and shear (4.3 MPa) strength limits at 99.95% reliability were expected for ongoing 30 m aperture telescopes. This study may improve the quality of opto-mechanical interfaces and reduce the risk on constructing extremely large telescopes.